Impacts of storage conditions on the dissolution performance of commercial metronidazole tablets available in Saudi Arabia - Basmah N. Aldosari; Areej M. Al-Mutairi; Alanood S. Almurshedi; Iman M. Alfagih; Bushra T. Al Quadeib; Eram Eltahir; Salma S. Almarshidy; Mohamed A. Ibrahim; Amal El Sayeh F. Abou El Ela (Elsevier, 2024)
This study aimed to investigate the impact of storage conditions on the dissolution performance of commercial metronidazole (MTZ) tablets available in Saudi Arabia; these were coded as the reference and Test A, Test B, and Test C products. Moreover, the hardness and the disintegration time were measured. The UV spectrophotometrically analytical technique was utilized to quantify MTZ. All the control tablets, which were tested upon receipt, met the USP requirement as not less than 85 % of the labeled amount of MTZ was dissolved in 60 min. The MTZ reference released 91.79 % ± 1.23 after 60 min, while the products A, B, and C released 87.96 % ± 2.60, 93.26 % ± 2.01, and 88.61 % ± 2.04, respectively. The different dissolution parameters calculated for all the control tablets showed that the MTZ products A and B had optimal dissolution performances and were considered similar to the reference product. The product C showed a significantly reduced dissolution performance and was considered different from the reference. The in vitro dissolution of the MTZ tablets stored at 40oC ± 2 oC/75 % RH ± 5 % for 6 months indicated that the tablets maintained compliance with the USP requirement. The MTZ reference released 89.36 % ± 3.64 after 60 min, while the products A, B, and C released 95.79 % ± 3.91, 88.52 % ± 2.52, and 87.79 % ± 5.04, respectively. However, a slight reduction in the percentage released after 30 min (% DE30) and a slight increase in the mean dissolution time (MDT) were observed during the first 3 months of storage under stressed conditions. These changes were more obvious after 6 months of storage under the same conditions. Furthermore, in vitro dissolution of the product C stored at 40oC ± 2 oC/75 % RH ± 5 % for 3 months with further protection against high humidity revealed an improvement in the dissolution parameters due to the similar protective effects exerted by the two packaging forms. Furthermore, the study shows that storage conditions such as humidity and temperature affect in vitro dissolution of MTZ marketed tablets which may have an impact on efficiency and patient safety.